ANALISIS AKSEBILITAS BAGI ANGKUTAN PENUMPANG PADA STASIUN PLABUAN BATANG - Lestari, Deswita Anggraini; Saraswati, Ratri Septina (Jurnal Teknik Sipil Giratory UPGRIS, 2026)
Accessibility in station buildings is very important because stations are public buildings used by many people. Accessibility that meets standards will make the station more orderly, efficient, and effective. Plabuan Station is experiencing problems because several supporting facilities are not provided or do not meet the applicable regulations. The existing facilities, such as waiting rooms and toilets, are inadequate, while other essential facilities like parking spaces, pedestrian pathways, health service rooms, and ramp facilities are not available. Therefore, it is recommended to expand the station to the east, improve the layout, add parking facilities on the west side, and ensure the station facilities comply with regulations and are universally accessible.